Escherichiacoli Nissle 1917 as a Novel Microrobot for Tumor-Targeted Imaging and Therapy - Qingyao Liu; Yongkang Gai; Yaqi Chen; Xiaoli Lan; Dawei Jiang (MDPI AG, 2021)
Highly efficient drug delivery systems with excellent tumor selectivity and minimal toxicity to normal tissues remain challenging for tumor treatment. Although great effort has been made to prolong the blood circulation and improve the delivery efficiency to tumor sites, nanomedicines are rarely approved for clinical application. Bacteria have the inherent properties of homing to solid tumors, presenting themselves as promising drug delivery systems. Escherichia coli Nissle 1917 (EcN) is a commonly used probiotic in clinical practice. Its facultative anaerobic property drives it to selectively colonize in the hypoxic area of the tumor for survival and reproduction. EcN can be engineered as a bacteria-based microrobot for molecular imaging, drug delivery, and gene delivery. This review summarizes the progress in EcN-mediated tumor imaging and therapy and discusses the prospects and challenges for its clinical application. EcN provides a new idea as a delivery vehicle and will be a powerful weapon against cancer.